Bacterial diversity in the western slopes of Mount Lawu, Karanganyar, Indonesia - RETNO ROSARIASTUTI; SUTAMI SUTAMI; SETYA NUGRAHA; BAMBANG SIGIT AMANTO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Rosariastuti R, Sutami, Nugraha S, Amanto BS. 2023. Bacterial diversity in the western slopes of Mount Lawu, Karanganyar, Indonesia. Biodiversitas 24: 2125-2133. Bacteria are an essential ecosystem component that is critical in nutrient recycling. Mount Lawu is an ecosystem with various habitats supporting bacterial growth. This region contains a diverse range of bacteria that has received little attention. This study aimed to investigate the bacterial biodiversity on Mount Lawu's western slopes of Karanganyar District, Central Java Province, Indonesia based on land use differences. There are five land uses including vegetable plantations, paddy fields, residential, mixed land, and forests. This study is exploratory-descriptive; the survey method and exploration technique are employed. Then, the Next Generation Sequencing (NGS) approach was administered to identify the type of bacteria. This research revealed more than 10 phylum and 28 species of bacteria. The diversity index (H') value was 8.80 for Vegetable plantations, 8.50 for paddy fields, 8.26 for mixed land, 8.10 for residential, and 7.66 for forests, with the highest bacterial diversity index in vegetable plantations. The bacterial diversity incorporates the phylum Proteobacteria, Methylomirabillota, Firmicutes, Actinobacteria, Verrucomicrobiota, Acidobacteriota, Bacteroidota, Myxococcota, Chloroflexi, and others. Phylum Proteobacteria was dominant in each land use, followed by Phylum Actinobacteria. The bacterial diversity on Mount Lawu's western slope was high. This study's findings are useful as a database (information) on microbial biodiversity in Central Java.